Effects of Unfermented and Fermented Tea Ofstrobilanthes Crispus on the Proliferation of Different Cancer Cell Lines - Teh, Arnida Hani (2006)
Strobilanthes crispus ZII 109 (L) Bremek or Saricocalix crispus ZII 109 (L) Bremek (Acanthaceae) plant is originated from Indonesia. Nowadays, more variation of teas, other than Camelia sinensis tea, are produced and marketed. Since interest has now moved to other 'teas', several experimental tests were carried out in order to fulfill these objectives: to develop fermented and unfermented teas of Strobilanthes crispus leaves, to evaluate the sensory qualities, to evaluate the macro and micro nutrient composition, to determine the total phenolics content, and to determine the antiproliferative effects of the prepared samples on several human cancer cell lines, i.e. liver cancer (HepG-2), hormone-dependent breast cancer (MCF-7), non-hormone-dependent breast cancer (MDA-MB-231), ovarian carcinoma (CAOV3) and human cervical carcinoma cell lines (HeLa). Generally, four different products were developed in this study; fermented Strobilanthes crispus tea (young leaves), fermented Strobilanthes crispus tea (old leaves), unfermented Strobilanthes crispus tea (young leaves), and unfermented Strobilanthes crispus tea (old leaves). Overall, the moisture content of all samples do not exceed 10%. Protein and fibre content of the samples are reported lower than the content in the fresh leaves. However these teas provide more carbohydrate and are high in ash levels. Calcium, sodium, potassium, magnesium, cuprum, ferum and iron are trace element present in all samples in various concentrations. Besides, the teas are also good sources of antioxidant vitamins (vitamin A, C and E), which correlate with the possible antioxidant activity. From all samples, fermented Strobilanthes crispus tea (old leaves) showed the highest level of vitamin A (p-carotene) value (2341.30 + 38.09 pg/g sample), while unfermented Strobilanthes crispus tea (old leaves) is rich in vitamin C (ascorbic acid equivalent = 5 177.88 f 1 13.96 pg/g sample) and vitamin E (a-tocopherol equivalent = 555.91 f 77.32 pg/g sample). While elemental analysis showed that carbon, oxygen, magnesium, aluminum, silicon, phosphorus, sulfur, chlorine, potassium, and calcium elements are present in all samples studied in various levels. The results might be different from the nutritional composition values because of the different mechanisms and methods of determination. The total phenolics content (ferullic acid equivalent) was found highest in unfermented Strobilanthes crispus tea (old leaves) (40.93583 + 0.70 mg/g of dried weight in methanol extract and 16.68333 f 0.53 mg/g of dried weight in water extract). Results from the antiproliferative studies showed that the fermented Strobilanthes crispus tea (old leaves) methanol extract, fermented Strobilanthes crispus tea (old leaves) water extract, unfermented Strobilanthes crispus tea (old leaves) methanol extract and unfermented Strobilanthes crispus tea (old leaves) water extract inhibited 50 % of the MCF-7 cell growth with ICso values = 23.0, 72.5, 63.0 and 80.5 yg/ml respectively, the unfermented Strobilanthes crispus tea (old leaves) methanol extract, unfermented Strobilanthes crispus tea (old leaves) water extract, fermented Strobilanthes crispus tea (young leaves) water extract, and fermented Strobilanthes crispus tea (old leaves) methanol extract, inhibited 50 % of the CAOV3 cell growth with Ic50 values = 54.12, 57.22, 13.91 and 67.39 pg/ml respectively, while unfermented Strobilanthes crispus tea (old leaves) methanol extract and unfermented Strobilanthes crispus tea (old leaves) water extract inhibited 50% of the HeLa cell growth with 1C50 values = 99.38 and 23.33 pg/ml respectively. On the other hand, sensory evaluation showed that the overall acceptability score was found highest for unfermented Strobilanthes crispus tea (old leaves), and this positively related with its ability to inhibit 50% of the proliferation of hormonedependent breast cancer (MCF-7), ovarian carcinoma cell lines (CAOV3) and human cervical carcinoma cell lines (HeLa) with ICso values less than 100 pg/ml. Generally, all the tea infusions were satisfactorily acceptable. Nonetheless, some of the values obtained for the different parameters for Strobilanthes crispus teas appear to fall within the range reported for other tea leaves and, in some cases, they are higher. Coupled with favorable amounts of minerals, fiber, vitamins, the various phenolic compounds, and the satisfactorily acceptable taste, colour, flavour and aroma, these teas may present a potential use as an herbal tea worth promoting for commercialization.